500 years of Saint Peter's - Radler, Axel.; Langner, Ingo.; Provobis (Firm); Kultur International Films (West Long Branch, NJ : Kultur, 2009)
April 18th, 1506, saw the beginning of the end for the 1200-year-old St. Peter's Basilica on the Vatican Hill in Rome. On this day, under the supervision of chief architect Donato Bramante, the foundation stone was laid for a new St. Peter's Cathedral.
DVD, region 1, NTSC, anamphoric widescreen (16:9) presentation; Dolby Digital 2.0.
Release date: Feb. 24, 2009.
Catalogued from web.
Keywords: Basilica di San Pietro in Vaticano -- History; Documentary films; Documentary